2016
DOI: 10.1111/eip.12343
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and at‐risk mental state for psychosis in 2102 prisoners: the case for early detection and early intervention in prison

Abstract: AimPrisoners exhibit high rates of substance use and mental health problems. In the present study we sought to gain detailed understanding of substance use among young prisoners to inform early detection and early intervention strategies in a prison setting. MethodsThis is a cross-sectional study of 2,102 prisoners who were screened by the London Early detection And Prevention in prison team (LEAP). Data on the use of substances were collected including age of first use, recent use, duration of use and poly-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This percentage was significantly higher (79%) for patients in the VP group. In line with Cooper et al [22], the mean age at which patients in the VP group began using cannabis was 15 years while it was 17 years in the NVP group (a figure consistent with previous studies [8,[53][54][55]). At program entry, while violent patients are 22 years old on average, the rates of CU remained significantly higher in VPs than in NVPs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This percentage was significantly higher (79%) for patients in the VP group. In line with Cooper et al [22], the mean age at which patients in the VP group began using cannabis was 15 years while it was 17 years in the NVP group (a figure consistent with previous studies [8,[53][54][55]). At program entry, while violent patients are 22 years old on average, the rates of CU remained significantly higher in VPs than in NVPs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, despite clinical and neurobiological evidence demonstrating the adverse effects of CU at a young age in psychosis, the impact of age at onset of CU on VB has not been well explored either in these patients. Although we observed in a previous paper that VPs had started using cannabis at an early age [27], and although studies in nonpsychotic adolescents have demonstrated a link between early CU and violence [36], only one study by Cooper et al [22], has focused specifically on the issue of age at onset of CU in violent prisoners. Their results showed that prisoners at high risk of developing psychosis started using cannabis before the age of 15, but the authors did not specifically explore the link between violence and early onset of consumption.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Despite country and study differences and variations in illicit drug use prevalence between men and women, the studies of this comprehensive literature confirm a high level of illicit drug use in European countries. The high prevalence may be linked to a high burden of drug-related problems in an already vulnerable population that frequently ends up in prison (Cooper et al, 2018;Decorte, 2007;Fazel et al, 2017). Prisons may be the first place where hard to reach people with drug problems who commit crimes can get in touch with drug rehabilitation programs (Alves et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Non-oral NMU of prescription stimulants-use that involves alternate routes of administration including intranasal or intravenous routes-has been reported in adolescents (18)(19)(20)(21), college students (22)(23)(24)(25), and adults (26)(27)(28). While the physical and psychiatric risks as well as mortality associated with prescription stimulant NMU have been considered (29)(30)(31)(32)(33)(34), less is known about non-oral prescription stimulant NMU, which can include adverse physical outcomes, such as toxicity or tissue damage (35)(36)(37)(38)(39)(40), and adverse mental health outcomes, such as anxiety or depression (41) or even psychosis (33).…”
Section: Introductionmentioning
confidence: 99%